New developments in nucleoside analogues biosynthesis: A review - Lapponi, María José (2016)
The present review deals with current advances in the chemoenzymatic synthesis of biologically important nucleoside analogues (NA), either by the use of microorganisms or enzymes as biocatalysts. The interest in exploiting these biocatalysts is constantly increasing nowadays because of the advantages they have with respect to classic organic chemistry synthesis, such as a fewer number of synthesis steps, an improved chemo-, regio- and stereoselectivity, high catalytic efficiency, and simple subsequent processing. Besides, this technology offers an environmentally friendly alternative in comparison with synthetic chemistry. Thus, the present article gives a brief outline of emerging methodologies for the biosynthesis of NAs commonly used in cancer therapies, such as cladribine, clofarabine, nelarabine, fludarabine, decitabine, cytarabine and floxuridine, and as antivirals: ribavirin, iduviran, vidarabine, acyclovir, lamivudine and emtricitabine from microbial or enzymatic sources, and their potential applications in the biotechnology industry. Also, it points highlights the importance of subsequent modifications of nucleoside analogues by different enzymes used as biocatalysts in order to improve the pharmacological properties of the existing drugs. Moreover, the importance of biocatalyst immobilization for industrial applications is considered.